Insights into uveitis from Brentuximab vedotin in refractory Hodgkin’s lymphoma: a case report and brief review - Liu, Mengyuan; Ren, Kexing; Ai, Ping; Zou, Liqun (Frontiers in Oncology, 2024)
Background: Brentuximab Vedotin (BV), an antibody-drug conjugate targeting CD30, has proven effective for treating refractory Hodgkin’s lymphoma. However, emerging data indicate potential for rare but significant ocular adverse events, including uveitis. This study aims to investigate the incidence of acute uveitis associated with BV through a detailed case report and a brief review of the literature on ocular side effects of BV. Case Report: We present a case of a 16-year-old male patient with refractory Hodgkin’s lymphoma who developed bilateral anterior and intermediate uveitis following BV therapy. The patient’s clinical course included the onset of ocular symptoms, such as blurred vision and eye pain, shortly after the initiation of BV. Management involved a combination of corticosteroids and discontinuation of BV. The patient experienced a partial improvement in ocular symptoms but had subsequent disease relapse, requiring alternative treatments. Literature Review: A review of the literature identified a small number of reports documenting ocular adverse events related to BV. The review discusses the clinical presentation of these adverse effects, their onset, and management strategies. Mechanistic insights into BV-induced uveitis suggest a role for the drug’s cytotoxic components and their impact on immune responses. Comparative analysis with other antibody-drug conjugates highlights the rarity of uveitis as a side effect but emphasizes the need for vigilance. Discussion: The case report underscores the importance of monitoring for uveitis in patients receiving BV, especially in the context of rare but serious adverse reactions. Recommendations for clinical practice include early recognition of ocular symptoms and consideration of alternative therapies in the case of severe uveitis. The study also suggests avenues for future research to explore the mechanisms behind BV-induced uveitis and improve management strategies. Keywords: Brentuximab vedotin, Hodgkin’s lymphoma, uveitis, MMAE， antibody-drug conjugate, case report